Comparative Study of Contagious Diseases in Clay County vs. Riley County: Diphtheria, Scarlet Fever, Smallpox, Typhoid Fever, 1907-1917 - Musgrove, Yates S. (Kansas State University, The Chapman Center for Rural Studies, 2010)
Analyzing contagious disease records kept by physicians in two contiguous Kansas counties, this study reaches interesting conclusions about the role of the railroads in early twentieth century Kansas. Rail lines are suspected disease vectors. The presence of Kansas State University also played a part in the spread of specific contagious diseases. The author presents data in statistical tables.
Yates S. Musgrove, “Comparative Study of Contagious Diseases in Clay County vs. Riley County: Diphtheria, Scarlet Fever, Smallpox, Typhoid Fever, 1907-1917,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/218.
Keywords: Clay County; Riley County; Manhattan; Kansas Pacific Railroad; Clay Center; Oakhill